The Use and Misuse of Income Data and Extreme Poverty in the United States - Meyer, Bruce D.; Wu, Derek; Mooers, Victoria; Medalia, Carla (Journal of Labor Economics, 2021)
Recent research suggests that the share of US households living on less than $2/person/day is high and rising. We reexamine such extreme poverty by linking SIPP and CPS data to administrative tax and program data. We find that more than 90% of those reported to be in extreme poverty are not, once we include in-kind transfers, replace survey reports of earnings and transfer receipt with administrative records, and account for ownership of substantial assets. More than half of all misclassified households have incomes from the administrative data above the poverty line, and many have middle-class measures of material well-being.